2019
DOI: 10.32709/akusosbil.553326
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Digital Game Playing Habits of Vocational School Students in Terms of Different Variables

Abstract: Bu araştırmada, meslek yüksekokulu öğrencilerinin dijital oyun oynama alışkanlıklarının cinsiyet, sınıf düzeyi, öğrenim gördükleri program, düzenli çevrimiçi oyun oynayıp oynamama durumları, dijital oyun oynama platformları, dijital oyun oynama yılları ve günlük dijital oyun oynama sürelerine göre incelenmesi amaçlanmıştır. Araştırmada tarama modeli kullanılmıştır. Araştırmanın katılımcılarını 2018-2019 eğitim öğretim yılında Sakarya Üniversitesi ve Sakarya Uygulamalı Bilimler Üniversitelerinin farklı Meslek Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…In the study conducted by Topal & Aydın (2018), digital game motivations were determined as stress relief and competition. Finally, in the study conducted by Bağcı (2019), the motivations of spending time and relieving stress came to the fore as the motivation of the digital game. Mobil devices P10 PC…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Topal & Aydın (2018), digital game motivations were determined as stress relief and competition. Finally, in the study conducted by Bağcı (2019), the motivations of spending time and relieving stress came to the fore as the motivation of the digital game. Mobil devices P10 PC…”
Section: Resultsmentioning
confidence: 99%
“…In their study concluded that the PC used first to play games, and mobile devices were used after the computer. In the research conducted by Bağcı (2019), it was determined that digital games are played more on mobile devices.…”
Section: Resultsmentioning
confidence: 99%
“…In their study concluded that the PC used first to play games, and mobile devices were used after the computer. In the research conducted by Bağcı (2019), it was determined that digital games are played more on mobile devices. When other studies on the time spent with digital games are examined, it was seen that in the study conducted by Ünal et al (2013), 59% of the participants stated that they played games for less than 1 hour a day.…”
Section: Resultsmentioning
confidence: 99%
“…These results are striking. It is reported that the internet and social media use is widespread among young people, and they mostly use social media to spend their free time, play internet games and watch TV (Bağcı, 2019). Young people have a lot of free time due to being at home in the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%